Phylogeographic analysis of filterable bacteria with special reference to Rhizobialesstrains that occur in cryospheric habitats - Nakai, Ryosuke; Shibuya, Eri; Justel, Ana; Rico, Eugenio; Quesada, Antonio; Kobayashi, Fumihisa; Iwasaka, Yasunobu; Shi, Guang-Yu; Amano, Yuki; Iwatsuki, Teruki; Naganuma, Takeshi (Antarctic Science, 2013)
Abstract Although the lower size limit of microorganisms was previously believed to be c . 0.2 μm, there is evidence for the existence of microorganisms that can pass through 0.2 μm-pore-size filters called ultramicrobacteria or nanobacteria. However, information on the phylogeny and biogeography of these bacteria is limited. We obtained 53 isolates of 0.2 μm-passable bacteria from 31 samples collected at 26 locations worldwide, including the Arctic Svalbard Islands, deserts, and Maritime Antarctica. Phylogenetic analysis of near full-length 16S rRNA gene sequences revealed that 18 of the 53 isolates were < 97% homologous with previously cultured isolates, representing potentially novel species. Two isolates (order Rhizobiales ) (100% identical) collected from Byers Peninsula, Livingston Island in Maritime Antarctica, were closely related (99.8% similarity) to an isolate collected from intertidal sediments in East Antarctica. In addition, the sequence of this Antarctic isolate showed ≥ 97% similarity to 901 sequences derived from known isolates and samples collected at geographically disparate locations under various environmental conditions. Interestingly, among 13 sequences showing ≥ 99% similarity, ten were isolated from cryospheric habitats such as Arctic, Antarctic, and alpine environments. This implies that such Rhizobiales strains occur in the cryospheric regions, however, their abundance and biomass may be scarce depending on the geographic location.